Review: Melastoma malabathricum Natural Compounds as Inhibitors of Resistant Bacterial Development - Susanti, Febria Elvy; Efdi, Mai; Syafrizayanti; Septama, Abdi Wira (Chempublish Journal, 2025)
The abundance of natural medicines in nature is very capable of being used and developed in various lives both individually and in combination in the modern medical field. Various developments and treatments as well as the discovery of new concepts will be able to interact with human physiology. One plant that has the potential to be developed is Melastoma malabathricum, also known as senduduk. This plant from the Melastomataceae family is easily found in tropical Asia and has long been used as an herb in traditional Chinese medicine. Based on the data collected, various studies have shown the pharmacological bioactivity of Melastoma malabathricum which has antibacterial potential and is able to fight resistant bacteria. Chemicals in this plant, including flavonoids, terpenoids, alkaloids, and steroids have been detected and shown to be inhibitors of bacterial growth, including resistant bacteria.